Terms of Reference for conducting a comparative analysis of diagnostic tools for National Evaluation Systems in Africa - CLEAR-AA (My University, 2023)
CLEAR-AA, DEval and WFP are collaborating to strengthen evaluation capacity development across the African Continent. At a kick-off workshop at the Evidence 2023 Conference in September 2023 in Entebbe, Uganda, the three partners agreed on the need for a deeper understanding of the landscape of diagnostic tools and processes, towards improving interventions focused on the strengthening or establishment of national M&E systems, and more specifically to help focus their work in Evaluation Capacity Development [ECD], particularly across the African continent.